Design and development of glass-reinforced polymeric composites using multi jet fusion process - Tey, Wei Shian (Nanyang Technological University, 2024)
The Hewlett-Packard (HP) Multi Jet Fusion (MJF) process is a recently emerged polymer powder bed fusion (PBF) additive manufacturing (AM) process that utilizes a combination of powder bed and inkjet printing to fabricate functional parts with voxel resolution. While the MJF technology offer several advantages over other PBF processes such as Selective Laser Sintering (SLS), MJF applications are limited to its small material palette of engineering polymers, which do not cater to applications where high performance is required. As research of MJF is still in its infancy, literature on the MJF materials and MJF printing mechanisms are scarce and do not provide sufficient depth to aid in the development of new MJF materials. Therefore, this Ph.D. research aims to provide an in-depth analysis of the existing MJF materials, provide some insight on the MJF printing mechanisms, and develop new high-performance composites using existing MJF materials as the polymer matrix.